Mapping Socio-Economic Vulnerability to Rob Flood Hazards in Coastal Cities, North Pekalongan District, Pekalongan City - Denis Said Mukhtar; Ahmad Zuhdi (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
Climate change brings danger to several areas, especially in coastal urban areas. One of them is the tidal flood which experienced inundation. Tidal floods pose a serious threat to the sustainability of social life and economic growth. Assessment of social and economic vulnerabilities is needed to overcome the risk of disaster hazards due to climate change in the form of coastal tidal floods in cities. This research is expected to be able to describe socio-economic vulnerability through the variables of population density, age, gender, occupation, and level of education to tidal floods that have occurred in 42% of the area. The research method used is quantitative analysis, scoring, and geographic information system modeling with village analysis units. The results showed that Panjang Baru Village was the most vulnerable area because of the high density and low-income levels of the people, most of whom were fishermen and farmers households. It also indicates the contribution of population density, level of education, and employment to the level of vulnerability. This study states that the socio-economic aspect is an important factor that must be considered for the sustainability of life and community adaptation to the threat of climate change, especially tidal floods.